Сабина на французской диете - Куликова Галина Михайловна (Особо смешной детектив, 2007)
Экземпляры: ф16 (20170823) / Инвентарный номер: 54314 / Цена: 15.00 / Сис.шифр: Р2 / Авт.знак: К 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6